Serologic assays for the detection and strain identification of Pteropine orthoreovirus - Harpal Singh; Masayuki Shimojima; Shuetsu Fukushi; Aiko Fukuma; Hideki Tani; Tomoki Yoshikawa; Satoshi Taniguchi; Ming Yang; Masami Sugamata; Shigeru Morikawa; Masayuki Saijo (Emerging Microbes and Infections, 2016)
Pteropine orthoreovirus (PRV), potentially of bat origin, is reported to be a causative agent of emerging respiratory tract infections among humans in Southeast Asia. We evaluated the efficacy of serologic assays using the major outer capsid and cell attachment proteins (CAP) of PRV strains in the screening, confirmation and identification of three groups of human PRV infections; Indonesian/Japanese, Indonesian/Hong Kong and Malaysian strains. The different serologic assays were tested using rabbit polyclonal antisera raised against these proteins of selected PRV strains, and validation was carried out using sera from a Miyazaki-Bali/2007 PRV-infected patient and the patient’s contacts. The results of this study showed that rabbit polyclonal antisera raised against the CAP of the Miyazaki-Bali/2007 PRV strain showed the highest reactivity to the Miyazaki-Bali/2007 PRV and to a lesser extent, cross-reactivity with the HK23629/07 and Melaka PRVs, respectively. Neutralization activity against the Miyazaki-Bali/2007 PRV was observed using rabbit anti-Miyazaki-Bali/2007 PRV CAP (320) but not with rabbit anti-HK23629/07 (<20) and Melaka (<20) PRV CAP. This lack of cross-neutralization, suggests the potential for human reinfection with different strains. The use of sera collected from contacts of the Miyazaki-Bali/2007 PRV-infected patient suggested that human-to-human infections with PRV are unlikely. Previously reported cases of PRV infections among human have been mild. However, the expanding geographic distribution of these viruses, of which its virulence remains unknown, warrants close monitoring to enable the development of prevention and control strategies in the event that a change in virulence occurs.Emerging Microbes and Infections (2016) 5, e44; doi:10.1038/emi.2016.35; published online 11 May 2016